1996
DOI: 10.1203/00006450-199604000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Soluble and Total Cellular L-Selectin in Cord Blood Is Associated with Its Impaired Shedding from Activated Neutrophils

Abstract: We have previously shown that surface levels of the adhesive glycoprotein, L-selectin, are diminished on cord blood neutrophils (polymorphonuclear leukocytes, PMN) and associated with impaired adherence to endothelium under flow conditions. To test the hypothesis that diminished surface levels reflect a total cellular deficiency, we measured L-selectin in PMN lysates and plasma from cord and adult blood. L-selectin content was decreased in cord blood PMN lysates compared with those of adults by both Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
8
23
2
Order By: Relevance
“…However, chemotactic stimulation with fMLP increased surface expression of CD11b to a greater degree in adult PMN than in cord blood PMN (Fig. 3), results that are similar to those we and others have observed (19,26,27).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, chemotactic stimulation with fMLP increased surface expression of CD11b to a greater degree in adult PMN than in cord blood PMN (Fig. 3), results that are similar to those we and others have observed (19,26,27).…”
Section: Resultssupporting
confidence: 91%
“…Dextran-sedimented leukocytes were subjected to density centrifugation, and the resultant was subjected to hypotonic lysis of contaminating erythrocytes, as previously described (19). Isolated PMN (10 6 cells/mL) suspended in RPMI 1640/2% FCS (Mediatech Inc., Herndon, VA) were cultured in polypropylene tubes at 37°C, 5% CO 2 , for up to 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…These factors make in vitro experiments with cord blood less accurate in pathophysiologic studies of MAS compared with adult blood experiments, which can be performed under strictly controlled conditions. It was shown previously that cord-blood neutrophils have lower CD62L expression compared with adult blood (48,49). Our data are in accordance with these observations.…”
Section: Discussionsupporting
confidence: 94%
“…Koenig et al (21) have reported that lysates of PMN from term neonatal cord blood have lower total L-selectin than adults, corroborating a cellular deficiency in the neonate. However, our findings of a similar loss of L-selectin compared with baseline between neonatal and adult neutrophils after FMLP stimulation differ from most previous studies, which have reported less shedding of L-selectin from neonates (4,5,21). We used high doses of FMLP, which may have masked differential losses at lower FMLP concentration.…”
Section: Discussioncontrasting
confidence: 86%